Determinants of Quality of Work Life - A win‐win Paradigm for Quality of Work Life and Business Performance - Swathi Kumari, Gajanethi (International Journal of Psychosocial Rehabilitation, 2024)
In today’s competitive world, the effective and efficient performance of employees gives the company its competitive edge. At the same time retaining them is becoming a major challenge to the HR Department. Salary and monetary benefits are no longer real retention factors; what is gaining importance is providing a quality of life for the employees. The service sectors are more challenging when compared to the other sectors in maintaining relations and job satisfaction of the employees. Quality of Work Life is one of the popular and global HR practices for retention and motivation of the employees; hence, in this context, it is found very relevant to study the quality of work life practices of the banking sector (public and private). The present paper aims to study and evaluate the opinion and perception of employees with regards to the quality of work life and also to give a keynote on the ASEAN & BRICS markets. A descriptive research study was conducted by choosing a stratified random sampling technique of 50 sample sizes in Hyderabad. The research could help to give solutions to the management regarding the quality of work life.